The Epidemiology of Major Depressive Episode in the Iraqi General Population. - Ali Obaid Al-Hamzawi; Ali Obaid Al-Hamzawi; Ronny Bruffaerts; Evelyn J Bromet; Abdulzahra Mohammed AlKhafaji; Ronald C Kessler (PLoS ONE)
Objective To assess the prevalence, symptom severity, functional impairment, and treatment of major depressive episode (MDE) in the Iraqi general population. Methods The Iraq Mental Health Survey is a nationally representative face-to-face survey of 4,332 non-institutionalized adults aged 18+ interviewed in 2006-2007 as part of the WHO World Mental Health Surveys. Prevalence and correlates of DSM-IV MDE were determined with the WHO Composite International Diagnostic Interview (CIDI). Findings Lifetime and 12-month prevalence of MDE were 7.4% and 4.0%, respectively. Close to half (46%) of the 12-month MDE cases were severe/very severe. MDE was more common among women and those previously married. Median age of onset was 25.2. Only one-seventh of 12-month MDE cases received treatment despite being associated with very substantial role impairment (on average 70 days out of role in the past year). Conclusions MDE is a commonly occurring disorder in the Iraqi general population and is associated with considerable disability and low treatment. Efforts are needed to decrease the barriers to treatment and to educate general medical providers in Iraq about the recognition and treatment of depression.